Предмет:
МатематикаАвтор:
анонимf(x)\' = (2 * (5x + 4)^(-1))’ = 2 * (5x + 4)’ * (5x + 4)^(-1)’ = 2 * ((5x)’ + (4)’) * (5x + 4)^(-1)’ = 2 * (5 + 0)’ * (-1) * (5x + 4)^(-2) = -10 * (5x + 4)^(-2) = -10 / (5x + 4)^2.
f(x)\' = ((-4x^3 + 1)^4 - (2 - x)^5)’ = ((-4x^3 + 1)^4)’ – ((2 - x)^5)’) = ((-4x^3 + 1)’ * (-4x^3 + 1)^4)’ – (2 - x)’ * ((2 - x)^5)’) = ((-4x^3)’ + (1)’) * (-4x^3 + 1)^4)’ – ((2)’ – (x)’) * ((2 - x)^5)’) = (-4 * 3 * x^2 + 0) * 4 * (-4x^3 + 1)^3 – (0 – 1) * 5 * (2 – x)^4 = -24x^2 * (-4x^3 + 1)^3 + 5 * (2 – x)^4.
f(x)\' = (x^(3 /2) – 2x^(-4))’ = (x^(3 /2))’ – (2x^(-4))’ = (3 / 2) * x^(1 / 2) – 2 * (-4) * x^(-5) = (3 / 2√x) + (8 / x^5).
f(x)\' = ((5x + 1)^(-3))’ = (5x + 1)’ * ((5x + 1)^(-3))’ = ((5x)’ + (1)’) * ((5x + 1)^(-3))’ = (5 + 0) * (-3) * (5x + 1)^(-4) = -15 * (5x + 1)^(-4) = -15 / (5x + 1)^4.
Автор:
heliodoroДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть